Follow me to the innovation frontier? Leaders, laggards, and the differential effects of imports and exports on technological innovation - Smith, Sheryl Winston (Journal of International Business Studies, 2014)
International trade and R&D offer significant opportunities for knowledge transfer through exports, but simultaneously increase potential competition through imports. In this paper, the author examines industry-level heterogeneity in the relationship between domestic innovation and international trade. Using a model of innovation in the global economy and a novel measure of relative industry strength, the paper examines differential effects of exports and imports in high-technology industries. These relationships are tested empirically using panel data from four high-technology industries in the US over the period 1973–2001. In industries that are relative global leaders, the empirical evidence points to gains from both exporting and importing. On the other hand, in industries that are relative global laggards, the results are more fluid. The author finds that exporting contributes favorably to domestic innovation in both leading and lagging industries when foreign R&D is at its maximum; at lower levels of knowledge abroad, however, the net effect of exporting on lagging industries is negative. Results for importing are likewise nuanced. In industries that are relative leaders, increasingly sophisticated imports lead to greater domestic innovation when industry structure is more concentrated, providing a competitive kick-start. In industries that are relative laggards, this effect is not present.